STYLISTIC SKILLS AS A COMPONENT IN THE FORMATION OF LANGUAGE PERSONALITY (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the problem of getting the stylistic norms in the process of forming the language personality. The linguistic and didactics aspect in the process of studying phonetic stylistics (rhythm and intonation structure of the speech, the cup hot phenomenon, the sound structure of expression) is defined.
Keywords: phonetic stylistics; the junctional aspect of language; rhythm and intonation structure of the speech; emphatic emphasis; euphony